(untitled) (Polish Yearbook of International Law, 2024)
This article explores the role of Lithuania in seeking accountability for Russia’s crimes in Ukraine since 2022. This small Baltic state, being both an EU and NATO member for twenty years now, is advocating on behalf of their Ukrainian colleagues in many international arenas and forums. However, more than two years into the brutal war, some organisational and legal challenges have started to emerge. These include the challenges resulting from the complex international institutional framework, as well as legal ones related to universal jurisdiction and the scope of crimes included under current criminal investigations.